Achieving cross curricular objectives through english language teaching in 7th grade in a public school - Faúndes Ascencio, Carolina (Universidad Católica del Maule, Facultad de Ciencias de la Educación, 2017)
Tesis para optar al grado de Licenciado en Lengua Inglesa